"And God1 Saw that it was Very Good": An Earth-friendly Theatrical Reading of Genesis 1. Issue 3 (November 2015) - Dube, Musa W.
Abstract : In the quest for an eco-justice reading, this article invites readers/listeners into a theatrical experience, where the drama of creation is staged. God enters the stage where the Earth is formless, dark and void, but covered by the Spirit of God. God begins to call various members of the Earth Community into being through God's own word over six days. They each come marching onto the stage. God views each created member and pronounces them good and finally pronounces all members to be very good. God gives the sun and the moon the power to rule the Earth. During the creation drama, God invites the Earth to the stage to give forth vegetation, water creatures and animals. The Earth thus does not only host all members of the Earth Community, but becomes the co-creator with God, and ensures continuity of creation. On the sixth day the Earth is no longer dark, void or formless, for there is light, atmosphere, sun, moon, stars, dry ground, seas, vegetation and living creatures of all sorts on the stage. God looks at them and says, "Let us make an earthling in our image, in our likeness". And thus a human being comes into being as a child of the Earth. The human being is told to keep the Earth Community just as good as God created it. Nonetheless, today's audience cannot watch the biblical drama of creation as an innocent spectator because the Earth is facing an environmental crisis from human exploitation. This article seeks to give an Earth-centred reading of Genesis 1 that does not entertain anthropocentric perspectives.